Study energy consumption, evaporation rate of the blue swimming crab hatchery system - Thongplu Suwapitchakorn; Jiamrittiwong Prayut; Puangngernmak Nutdechatorn (E3S Web of Conferences)
The rising demand for blue swimming crab products has led to a decrease in their coastal populations. The Blue Crab Bank Project was launched to counteract this decline. This study aims at the energy consumption, seawater evaporation rate, and dissolved oxygen levels at different airflow rates of 2 l/min and 3 l/min. The results indicate that the airflow rates lead to a reduction in evaporation rates by 6.39% and 4.53%, respectively, without significantly affecting salinity levels. The study also finds that energy consumption for incubating crab eggs at 2 l/min is 0.025 kWh per crab, which is significantly lower (24.24% reduction) than at 3 l/min. Additionally, the dissolved oxygen level at the lower flow rate is 7.0 mg/l. These findings highlight the effectiveness of lower flow rates in reducing energy consumption and maintaining optimal environmental conditions for crab egg hatching, which can help in sustaining the population of blue swimming crabs and support the livelihoods of coastal fishermen.